Shock-Associated Systemic Inflammation in Amniotic Fluid Embolism, Complicated by Clinical Death - Anatoly Brazhnikov; Natalya Zotova; Liliya Solomatina; Alexey Sarapultsev; Alexey Spirin; Evgeni Gusev (Pathophysiology, 2023)
Background: Amniotic fluid embolism (AFE) is one of the main causes of maternal mortality in developed countries. The most critical AFE variants may be considered from the perspective of systemic inflammation (SI), a general pathological process that includes high levels of systemic inflammatory response, neuroendocrine system distress, microthrombosis, and multiple organ dysfunction syndrome (MODS). This research work aimed to characterize the dynamics of super-acute SI using four clinical case studies of patients with critical AFE. Methods: In all the cases, we examined blood coagulation parameters, plasma levels of cortisol, troponin I, myoglobin, C-reactive protein, IL-6, IL-8, IL-10, and TNF-α, and calculated the integral scores. Results: All four patients revealed the characteristic signs of SI, including increased cytokine, myoglobin, and troponin I levels, changes in blood cortisol, and clinical manifestations of coagulopathy and MODS. At the same time, the cytokine plasma levels can be characterized not only as hypercytokinemia, and not even as a “cytokine storm”, but rather as a “cytokine catastrophe” (an increase of thousands and tens of thousands of times in proinflammatory cytokine levels). AFE pathogenesis involves rapid transition from the hyperergic shock phase, with its high levels of a systemic inflammatory response over to the hypoergic shock phase, characterized by the mismatch between low systemic inflammatory response values and the patient’s critical condition. In contrast to septic shock, in AFE there is a much more rapid succession of SI phases. Conclusion: AFE is one of the most compelling examples for studying the dynamics of super-acute SI.